Energy storage in isolated electrical system - Miguel, Miguel José Rodrigues Teixeira; Nogueira, Teresa Alexandra Ferreira Mourão Pinto (Neutro à Terra, 2021)
Energy storage has become a key issue in management of any renewable energy system. That is even more important in an isolated electrical system, as is the case with island system, due to the inherent fluctuating operation and inaccurate energy forecast. The growth of the decentralized generation in an isolated electrical grid means load stability problems and requires energy storage as a potential solution to guarantee safety and reliability standards. The study described in this paper highlights the need to store energy in Madeira island electrical system and evaluate the technical and environment benefits with the introduction of batteries to strengthen power network. A simulation tool was developed, suitable to quantify the impact of batteries in wind energy and thermal power plants existing technologies. This tool also allows the graphical analysis of the daily production, as well as the evolution of the power and energy in battery.